Integrated process for extraction and purification of alcohol dehydrogenase from Baker's yeast involving precipitation and aqueous two phase extraction - Madhusudhan, M. C.; Raghavarao, K. S. M. S.; Nene, Sanjay (Biochemical Engineering Journal, 2008)
The potential of aqueous two phase extraction for the purification of alcohol dehydrogenase (ADH) from Baker's yeast (Saccharomyces cerevisiae) is demonstrated. An integrated process involving precipitation followed by aqueous two phase extraction (ATPE) is used for effective recovery of the enzyme. This is carried out in two schemes. In the first scheme, ammonium sulphate precipitation is carried out followed by ATPE of the precipitate after suspending it in buffer. While the second scheme involves polyethylene glycol precipitation followed by ATPE of the supernatant. The effect of various process parameters such as molecular weight of polymer, tie line length, phase volume ratio and neutral salt is investigated for enhancing the activity recovery of ADH. First scheme resulted in about 85% enzyme activity recovery of ADH with purification factor of 4.2 while the second scheme about 90% enzyme activity recovery with 6.6-fold purification. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Alcohol dehydrogenase; aqueous two phase extraction; enzyme extraction; Precipitation; Purification; Yeast

Encapsulation of yeast (Saccharomyces cereviciae) by spray drying for extension of shelf life - Chandralekha, A.; Tavanandi, A. Hrishikesh; Amrutha, N.; Hebbar, H. Umesh; Raghavarao, K. S. M. S.; Gadre, Ramchandra V. (Drying Technology, 2016)
The objective of the present work was to encapsulate yeast using different carrier materials and examine their efficacy in retaining viability of cells after spray drying. Slurry containing yeast cells along with known amount of carrier material (maltodextrin, corn starch, gum arabic, acacia gum, polyethylene glycol 8000, -cyclodextrin, and skimmed milk powder, one at a time) was added and served as feed. Among these carrier materials attempted, corn starch and maltodextrin showed the best results with respect to powder yield (59%, w/w) and cell survival (80.5%), respectively. However, considering both survival and powder yield (67 and 59% w/w, respectively), corn starch was observed to be the most suitable carrier material.
Keywords: Cell viability; Encapsulation; freeze-drying; spray drying; Yeast

Nonconventional method for drying of Pseudomonas aeruginosa and its comparison with conventional methods - Umashankar, K.,; Chandralekha, A.; Dandavate, T.,; Tavanandi, H. A.; Raghavarao, K. S. M. S. (Drying Technology, 2018)
In this study, preparation of dried cultures of Pseudomonas aeruginosa using nonconventional drying method, namely, low-temperature low-humidity (LTLH) drying was investigated. The effect of carrier materials (whey protein, corn starch, and trehalose) was examined one at a time and also in combinations (to explore the synergistic effect). The results were compared with those obtained using spray drying and freeze drying in terms of cell survival and dry cell powder yield. The powder samples were analyzed also for morphology, flowability, particle size, and moisture content. In LTLH drying, good cell survival was observed along with high powder yield when compared with that in spray drying. Corn starch showed the highest cell survival (91%) and powder yield (94%, w/w) among the carrier materials employed besides resulting in good cell survival (65%) even after a storage period of 6 months.
Keywords: cell survival; Encapsulation; freeze drying; Low-temperature low-humidity (LTLH) drying; Pseudomonas aeruginosa; spray drying